2018
DOI: 10.2174/1567205015666180507104755
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Suppressor of Cytokine Signaling 3 in Microglia by Cinnamic Acid

Abstract: Neuroinflammation plays an important role in the pathogenesis of various neurodegenerative diseases including Alzheimer’s disease (AD). Suppressor of cytokine signaling 3 (SOCS3) is an anti-inflammatory molecule that suppresses cytokine signaling and inflammatory gene expression in different cells including microglia. However, pathways through which SOCS3 could be upregulated are poorly described. Cinnamic acid is a metabolite of cinnamon, a natural compound that is being widely used all over the world as a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…To verify the effect of tested compounds on NF-κB activity, the secretion of TNF-α, which is under its transcription control [44], was measured. CA is known for its ability to attenuate the production of this pro-inflammatory cytokine in vitro and in vivo [45,46]. In our experiment, pure CA did not affect the TNF-α production, see Figure 7.…”
Section: Inhibition Of Tnf-α Secretionmentioning
confidence: 47%
“…To verify the effect of tested compounds on NF-κB activity, the secretion of TNF-α, which is under its transcription control [44], was measured. CA is known for its ability to attenuate the production of this pro-inflammatory cytokine in vitro and in vivo [45,46]. In our experiment, pure CA did not affect the TNF-α production, see Figure 7.…”
Section: Inhibition Of Tnf-α Secretionmentioning
confidence: 47%
“…In vitro studies have shown that upregulation of SOCS3 by cinnamic acid suppressed expression of iNOS, TNF-a, IL-1b, and IL-6 in LPS-triggered mouse BV-2 microglia. 88 Studies in LysMCre-SOCS3 fl/fl mice, which lack SOCS3 expression in myeloid lineage cells, demonstrated enhanced polarization of microglia towards a pro-inflammatory state as demarcated by increased production and secretion of TNF-a, IL-1b, IL-6, CCL3, CCL4, and CXCL11. 89 Histone H3K27me3 demethylase Jumonji domain containing 3 (Jmjd3) also plays a pivotal role in microglial polarization towards an anti-inflammatory phenotype.…”
Section: Dynamic Transition Between Microglia Activation Statesmentioning
confidence: 99%
“…Acute phase response (APR) organs include the brain (involved in the increased synthesis of corticotropin-releasing hormone (CRH) and adrenocorticotropic hormone (ACTH), liver (involved in the increased synthesis of metallothionein and antioxidants to restore homeostasis of plasma proteins), bone marrow (increased thrombocytosis and reduced erythropoiesis), adrenal gland (increased cortisol production), and muscle (proteolysis) and adipose cells (altered lipid metabolism) (Robinson et al, 2016). The APR is regulated via interleukin 1 receptor antagonist (IL-1RA), IL-10, suppressor of cytokine signaling (SOCS) proteins, and transient expression of APP and their mRNA half-lives (McCormick et al, 2016; Chakrabarti et al, 2018). There are ~200 different APPs in animals.…”
Section: Acute Phase Proteinsmentioning
confidence: 99%